The Role of Organizational Communication in Improving the Quality of Service at a Beauty Clinic - Sofiah Ranti; Budi Suswanto; Hamluddin Hamluddin (Fakultas Komunikasi, Sastra, dan Bahasa, 2024)
Communication in an organization is a communication process that involves superiors, subordinates and other stakeholders in the organization. In an organization, communication is important in improving the quality of service, as is done by a beauty clinic in Bekasi, Indonesia. Therefore, this research aims to analyze the role of organizational communication in improving service quality. This research uses a constructivist paradigm. Apart from that, this research design is descriptive qualitative in which this research aims to investigate the circumstances, conditions, existence of the research site, and others that have been mentioned and explained in the form of a report. The instruments of this research are observation, interviews and documentation. The results of the present research show that the quality of beauty clinic services can be considered good because of the role of good organizational communication. In this case, communication actors work together to achieve good organizational goals.